Language policy, homelessness and neoliberal urbanization: The case of San Francisco's Union Square. (June 2016) - Wee, Lionel
Abstract : One example of the impact of neoliberalism on urbanization is that of the Business Improvement District (BID), where business and property owners collectively manage a district to ensure that it has an appropriate 'business climate'. The responses of BIDs to the language practices of the homeless, such as panhandling, tend to be ambivalent because homelessness is an issue that requires sensitivity. Nevertheless, overly aggressive panhandling can have adverse repercussions for businesses. This paper focuses on San Francisco's Union Square, which is the city's commercial retail center, and makes two key points. One, language policy needs to be viewed as planned, unplanned or transgressive, where these characterizations are necessarily from the perspective of an specific actor, such as the Union Square BID. Two, there are interesting attempts to transform panhandling practices from above, pushing these towards neoliberalism with the consequence that the panhandlers themselves sometimes respond by reimagining panhandling as work or a business.